2011
DOI: 10.1002/stem.725
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Anemia Caused by Viruses

Abstract: Most of the viruses known to be associated with anemia in human tend to persistently infect their host and are noncytopathic or poorly cytopathic for blood cell progenitors. Infections with Epstein-Barr virus, cytomegalovirus, varicella-zoster virus, human herpes virus 6 (HHV-6), B19 parvovirus, human immunodeficiency virus, hepatitis A and C viruses and the putative viral agent associated with non-A-G post-hepatitis aplastic anemia have been reported in association with anemia. Nevertheless, a direct cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Another retrospective study of 21 healthy, adult patients with HPV-B19 infection included 4 males and 17 females [23]. In humans, the genetic background probably accounts for the different patterns of HPV-induced anemia, and host genes may regulate the outcome of HPV-B19-induced aplastic crisis [28]. One may speculate that a correlation exists between genetic differences and gender gap in association with susceptibility to HPV infection, although very little is known with regard to this field.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study of 21 healthy, adult patients with HPV-B19 infection included 4 males and 17 females [23]. In humans, the genetic background probably accounts for the different patterns of HPV-induced anemia, and host genes may regulate the outcome of HPV-B19-induced aplastic crisis [28]. One may speculate that a correlation exists between genetic differences and gender gap in association with susceptibility to HPV infection, although very little is known with regard to this field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no cytopathic effect was observed which might be related to the relatively low number of infected cells in vitro . The absence of visible cytopathic effect does not exclude that this virus is indeed pathogenic in vivo, since many viruses do not cause visible cytopathic effect but are still pathogenic [31,32]. In addition to the brain, Seal parvovirus DNA was detected in various other tissues, including the lung, the liver and the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, preliminary experiments indicated that ZIKV infection of CD34 + HSPCs did neither inhibit cell growth nor prevented differentiation of erythroid and megakaryocytic cells (data not shown) as it is reported for other viruses such as DENV. [81][82][83][84] Thus, we speculate that thrombocytopenia and anemia in ZIKV-infected patients might be explained by cell damage due to an overshooting immune response 84,85 or ZIKV-induced impairment of blood vessel integrity or development [86][87][88] rather than by a direct interaction of ZIKV with erythroid and megakaryocytic cells. However, further investigations are crucial to unravel the connection of ZIKV pathogenicity and symptoms manifestation towards the prevention and cure of ZIKV infections.…”
Section: Discussionmentioning
confidence: 94%